In situ ATR-IR study on the photocatalytic decomposition of amino acids over Au/TiO2 and TiO2 - Dolamic, Igor; Bürgi, Thomas (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
The photocatalytic degradation of l-asparagine and l-glutamic acid over Au/TiO2 and TiO2 catalysts was investigated in situ by attenuated total reflection infrared (ATR-IR) in combination with modulation excitation spectroscopy. Oxalate was detected on the catalyst surface, which has not been reported before for degradation of amino acids by studies focusing on intermediates in solution. The ATR-IR spectra provide valuable information on the fate of the nitrogen. Ammonium was detected, in agreement with previous studies. Most importantly, strong signals of cyanide were observed, and this assignment has been corroborated by 15N labeling experiments. Cyanide was not reported before, to the best of our knowledge, for the photocatalytic degradation of amino acids. Cyanide was formed in the presence and the absence of gold particles on the TiO2 surface. The cyanide leads to leaching of gold via Au(CN)2− species that were detected in solution by mass spectrometry.